2016
DOI: 10.1039/c5ce02332g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a series of aCTV-based covalent organic frameworks and substituent effects on their properties

Abstract: A series of amino substituted cyclotrianisylene (aCTV)-based covalent organic frameworks (COFs), aCTV-COF1 to aCTV-COF4, have been synthesized. These crystalline analogues showed permanent porosity with BET surface areas from 656 m 2 g −1 to 1428 m 2 g −1 . With the introduction of methoxy groups and hydroxyl groups at the phenyl linker moieties in aCTV-COF3 and aCTV-COF4, their properties (such as color, gas adsorption, hydrolytic stability and so on) have been influenced to a great extent. The CO 2 sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…[ 90 ] It was found that the introduction of methoxy and hydroxyl groups into the well‐defined frameworks can make positive efforts toward H 2 adsorption. [ 91 ] Moreover, borate‐linked COFs were derived from CTC and 4,4′‐biphenyldiboronic acid or pyrenediboronic acid. [ 33 ] McKeown and co‐workers incorporated CTC into the network of PIM by the S N Ar reaction between CTV and TFN.…”
Section: Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 90 ] It was found that the introduction of methoxy and hydroxyl groups into the well‐defined frameworks can make positive efforts toward H 2 adsorption. [ 91 ] Moreover, borate‐linked COFs were derived from CTC and 4,4′‐biphenyldiboronic acid or pyrenediboronic acid. [ 33 ] McKeown and co‐workers incorporated CTC into the network of PIM by the S N Ar reaction between CTV and TFN.…”
Section: Separationmentioning
confidence: 99%
“…Afterward, the same group further explored other types of CTV-based crystalline COFs, including imine-linked COFs and borate-linked COFs. [33,90,91] Iminelinked COFs could be synthesized from triformyl-CTV and aromatic amines, or the condensation of amino-CTV and aromatic aldehydes. Compared with amorphous POPs, crystalline CTC-based COFs have a higher H 2 uptake capacity of 1.3 wt% at 823 mm Hg and 1.23 wt% at 760 mm Hg.…”
Section: H 2 Storagementioning
confidence: 99%
“…Commonly, the topology design is realized by use of planar and tetrahedral units as knots to connect with appropriate linkers to form 2D and 3D COFs, respectively. So far the building units are limited to multisubstituted arenes and few macrocyclic skeletons. Meanwhile, discrete organic cages possessing intrinsic cavity and porosity have received great interests in past decades . The use of such cages as building units to construct extended networks, the cage-to-framework strategy, is particularly appealing.…”
mentioning
confidence: 99%
“…The high crystallinity was attributed to the ability of the bowls to stack in the 2D COF. CTVs have also been introduced in imine‐linked COFs from the triformyl–CTV [ 26 ] and triamine–CTV [ 27 ] derivatives, leading to COFs with moderate crystallinity.…”
Section: Shape‐persistent Monomersmentioning
confidence: 99%